Meeting oxygen requirements of rural India: A self-contained solution - Nirupam Madaan; Biraj Chandra Paul; Randeep Guleria (Wolters Kluwer Medknow Publications, 2021)
Addressing oxygen requirements of rural India should aim at using a safe, low-cost, easily available, and replenishable source of oxygen of moderate purity. This may be possible with the provision of a self-sustaining oxygen concentrator (pressure swing adsorption with multiple molecular sieve technology) capable of delivering oxygen at high-flow rates, through a centralized distribution system to 100 or more bedded rural hospitals, with back up from an oxygen bank of 10 × 10 cylinders. This will provide a 24 × 7 supply of oxygen of acceptable purity (~93%) for the treatment of hypoxemic conditions and will enable hospitals to specifically provide for high-flow oxygen in at least 15% of the beds. It may also serve as a facility for a local refill of oxygen cylinders for emergency use within the hospital as well as to subsidiary primary health centers, subcenters, and ambulances, thereby nudging our health-care system toward self-sufficiency in oxygen generation and utilization.